The Jews - Wijnberg, Nachoem M. (punctum books, 2016)
The Jews is an anti-historical thriller in the form of a Talmudic tragicomedy, taking place sometime during the Second World War. Stalin and his Minister of Security Beria are worried about the political developments in Germany, where Martin Heidegger has replaced Adolf Hitler as Chancellor of the Third Reich. Suspecting that the Frankfurt School, headed by Vice-Chancellor Walter Benjamin, has masterminded this takeover, he dispatches two Jewish actors, Salomon Maimon and Natalia Goncharova, to investigate the situation in the hope of uncovering the extent of the Jewish conspiracy. Upon arrival in Berlin, Maimon and Goncharova are received by Benjamin, who introduces them to Heidegger. The latter has stopped speaking to anyone except his mother since his rise to power, and Benjamin holds long speeches on the history of theater, the law, God, the royal gods and the old goddesses. Eventually, prodded by his mother, Heidegger marries Goncharova, surrounded by a merry audience. The novel ends on a plain somewhere between Moscow and Berlin, where the final battle for Jerusalem is being waged. In front of the entrance of a camp, Maimon and Benjamin are joined by a group of old Jews arriving by train, bringing the news of Stalin's death by circumcision. They reenact scenes from the Old Testament while Jerusalem is burning. Did the world to come finally arrive?